Parallel visual data restoration on multi-GPGPUs using stencil-reduce pattern. (November 2015) - Aldinucci, Marco; Pezzi, Guilherme Peretti; Drocco, Maurizio; Spampinato, Concetto; Torquati, Massimo
In this paper, a highly effective parallel filter for visual data restoration is presented. The filter is designed following a skeletal approach, using a newly proposed stencil-reduce, and has been implemented by way of the FastFlow parallel programming library. As a result of its high-level design, it is possible to run the filter seamlessly on a multicore machine, on multi-GPGPUs, or on both. The design and implementation of the filter are discussed, and an experimental evaluation is presented.